How many legs? - Drew, David (Nelson Australia South Melbourne, 1994)
"How Many Legs?" is a playful and engaging children's book that explores counting through various animals and their legs. Each page introduces different creatures, inviting readers to guess how many legs each one has. The rhythmic text and colorful illustrations make it fun for young readers as they learn about numbers and animal diversity.